Perancangan Next Generation OPAC Berbasis Library 2.0 (Next Generation OPAC Design Based on Library 2.0) - Toni Afandi; Wisnu Ananta Kusuma; Janti G. Sudjana (Jurnal Pustakawan Indonesia, 2014)
ABSTRACTLibrary catalogue is challenged by the development of web technology that produce search engines dan also has change users’ interaction with information in this Web 2.0 enviroment. Users expect to participate and collaborate in the creation of information. This study aims to create a prototype of next generation OPAC which will use users’ contribution as an enrichment to OPAC. Users can contribute information to existing bibliographic record with tagging, rating and comment. Prototype was created using Drupal 7 and tested using Black Box method. Testing results shows that this prototype can fufill all functional requirements.Keywords: next generation OPAC, Web 2.0, Library 2.0, tagging, rating, review.